Run & roll conceptual business for courier service - Mohamad Abdul Nasir, Muhammad Nazhan; Ajemeek, Ameerul Afiqeen; Hammad, Khairul Ikhwan; Ahmad Dahlan, Abdul Rahman (Research Publish Journal, 2018)
The purpose of this paper is to provide a conceptual business solution for courier services. This paper will also contribute to the courier service market and transporter market. The application, Run&Roll, will be based on an on-demand delivery service that targets to make on-demand delivery services a norm in Malaysia and eventually throughout the world. Run&Roll will not just deliver food products, but also merchandises and a transporter service. The drivers can be the consumers and vice versa. Literature Review, benchmarking, Business Model Canvas (BMC), 4 Lenses of Innovation, and Value Proposition Design (VPD) have been used as the methodologies for this paper.